ACTIVITY OF ACID AND ALKALINE PHOSPHATASES IN THE EGGS OF SOME FRESHWATER TELEOSTS - Shaffi, S A; Jafri, A K (Indian Journal of Fisheries, 2011)
Litfle attention has been paid in the past to the localization and measurement of various enzymatic activities of fish egg with a view to understanding its metabolic activity. In an earlier communication from this laboratory the activity of two phosphomonoesterases, the acid and alkaline phosphatases, v(?ere described in the ripe, unspawned eggs of a few species of freshwater fishes (Jafri and Khawaja, 1967a). The studies on the activities of these enzymes were later extended to the eggs of some more fishes, as a continuatioo of earlier work, and the results have been described in the present paper. It its-hoped that the present set of experiments would yield additional information on fish phosphatases and would be interesting from the standpoint of comparative biochemistry and physiology.